GMOs, safety concerns and international trade: developing countries' perspective - Laxman, Lekha; Ansari, Abdul Haseeb (Emerald Group Publishing, 2011)
Developing countries are keen to venture into biotechnology and benefit from genetically modified organisms (GMOs) by them and by others. Agricultural biotechnology is relatively more important for them because in future their population will keep on growing. While joining the biotechnology race, especially in the agricultural sector, it is important for them to weigh the benefits against the risks in production and use of GMOs. It is for this reason that applications of the ‗precautionary principle‘ and ‗risk assessment‘ have got inroads. Thus, not only do we need to know potential threats to the biodiversity, but we also need to consider the imperatives of protecting human health of present and future generations and sustainable development. Significant biosafety issues relating to the introduction of GMOs in the environment and human consumption, and consequent loss of agricultural biodiversity need to be addressed especially in relation to the developing and least developed nations in the pursuit of trade in GMOs. Most of these nations have not formulated adequate legal and institutional frameworks supported with necessary expertise to regulate, monitor and ensure safety of GMOs, especially agricultural GMOs produced and imported by the. This paper discusses the impact of agricultural biotechnology in developing and least developed countries and attempts to address the existing biosafety concerns that might have an impact on trade and the environment whilst highlighting the importance of choosing development pathways that are conducive to the specific needs of these nations without endangering their biodiversity and health of their people